Are Village Animal Health Workers Able to Assist in Strengthening Transboundary Animal Disease Control in Cambodia?. Issue 2 (31st October 2015) - Stratton, J.; Toribio, J‐A. L. M. L.; Suon, S.; Young, J. R.; Cowled, B.; Windsor, P. A.
Summary: A cross‐sectional survey of 445 Village Animal Health Workers (VAHWs) from 19 provinces in Cambodia was undertaken. The aim was to establish their levels of training, farm visit frequency, reasons for visits and disease reporting practices, enabling the strengths and weaknesses of the VAHW system in Cambodia to be determined, in providing both a fee‐based smallholder livestock clinical service and a government partnership in transboundary animal disease (TAD) surveillance and control. The study used 'guided group interviews' and identified that VAHWs had good contact with farmers with 61.5% making more than one farm visit daily. However, incomes from services remained low, with 45% VAHWs obtaining between 20 and 40% of their household income from VAHW activities. VAHWs recorded relatively high rates of disease reporting, with 72% claiming they report diseases immediately and 74% undertaking monthly reporting to veterinary authorities. Logistic regression analysis revealed VAHW contact frequency with district and/or provincial officers was associated with more VAHW farm visits, and frequency of VAHW visits to smallholder farms was positively associated with average monthly expenditure on animal medication and equipment. This suggests that increased veterinary extension to VAHWs and access to veterinary equipment, vaccines and drugs may further increase VAHW‐farmer engagement. VAHWs provide an accessible, market‐based, animal health 'treatment and reporting' service linked to livestock smallholders across Cambodia. However, for improved TAD prevention and more efficient control of outbreaks, research that assesses provision of an animal health 'preventive‐based' business model is urgently needed to reduce both the costs to farmers and the risks to the economy due to foot‐and‐mouth disease and other TADs in Cambodia.